Some Aspects of the State-of-the-Arts in Biomedical Science Research: A Perspective for Organizational Change in African Academia (Nigerian Journal of Physiological Sciences, 2021)
Summary: In the biomedical sciences, there is need to generate solutions for Africa’s health and economic problems through the impact of university research. To guide organizational transformation, the author here presents some aspects of the state-of-the-arts of biomedical science research in advanced countries using a perspective derived from the FASEB journal publications. The author examines the thirty three peer reviewed scientific research articles in a centennial (April 2012) issue of the FASEB Journal [Volume 26(4)] using the following parameters: number of authors contributing to the paper; number of academic departments contributing to the paper; number of academic institutions contributing to the paper; funding of the research reported in the article. The articles were written by 7.97±0.61 authors from 3.46±0.3 departments of 2.79±0.29 institutions. The contributors were classified into four categories: basic sciences, clinical sciences, institutions and centers, and programs and labs. Amongst the publications, 21.2% were single disciplinary. Two tier collaboration amongst any two of the four categories were observed in 16/33 (48.5%) of the articles. Three tier and four tier collaborations were observed amongst 7/33 (21.2%) and 3/33 (9%) of the articles respectively. Therefore 26/33 (78.7%) of the articles were multidisciplinary. Collaborative efforts between basic science and clinical science departments were observed in 9/33 (27.3%) articles. Public funding through government agencies provided 85 out of a total of 143 (59.5%) grants. The collaborative and multidisciplinary nature and government support are characteristic of biomedical science in the US where research tends to result in solutions to problems and economic benefits.
Keywords: Organizational Change; Biomedical Science; FASEB; Biomedical Research; Nigeria; Africa